High Temperature Superconductivity: A Prospective Remedy for Energy Crisis in Future - Gnawali, Chhabi L.; Pandey, Binod (Journal of the Institute of Engineering, 2021)
This paper summarizes the superconducting phenomenon followed by application of superconductivity devices on energy sector. High temperature superconductivity are very innovative, promising and eco-friendly alternative to mitigate the energy crisis by saving energy.